PERANAN ACTIVITY-BASED COSTING SYSTEM DALAM MENGANALISIS LABA PER PELANGGAN UNTUK MENINGKATKAN LABA DEPARTEMEN PRINTING PT TJ. - Arthur Purboyo; Aileen Kurniawan (Center for Economic Studies Universitas Katolik Parahyangan, 2007)
Many managers think that increases in sales will automatically increase company's profit. With this assumption, the company will accept order from customer without making judgment on the capacity of company consumed by that order. The background of this thinking is catted volume-related. But, in many cases, cost depends on the activity consumed to accomplish an order. So, cost allocated based on unit of output sometimes will cause overcosted or undercosted. On of the solution to over or undercosted is cost allocation based on activity consumed by the product or the order. This cost allocation is called activity-based costing. Activity-based costing systems help will provide complete and accurate information that are needed by the management to make better decision based on cost of an order.Keywords: overcosted, undercosted, activity-based costing, activity based management